Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Rumah Sakit Umum Daya Makassar - Dandy Yusmar; Abdullah Abdullah; Andi Novita Paramitha (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This research aims to determine the influence of work motivation and discipline on employee performance at the Daya Makassar Hospital Office. The object of this research is the Makassar Daya Hospital Office. The data used in this research is primary data with a sampling method using simple random sampling and a data analysis method using multiple linear analysis, while the sample taken was 45 employees. The results of this research have been tested for validity, and classical assumptions in the form of normality assumptions, multicollinearity assumptions and heteroscedasticity assumptions have also been tested. The data analysis method uses multiple linear regression analysis techniques and hypothesis testing. The results of this research show that the Motivation variable (X1) has a positive and significant effect on Employee Performance, Work Discipline (X2) has a positive and significant effect on Employee Performance, Motivation and Work Discipline simultaneously have an effect on Employee Performance (Y).